2016
DOI: 10.4081/itjm.2016.639
|View full text |Cite
|
Sign up to set email alerts
|

Adenoid ameloblastoma with dentinoid and cellular atypia: a rare case report

Abstract: Adenomatoid odontogenic tumor (AOT) is always a benign tumor with rare incidence of recurrence while ameloblastoma is the commonest gnathic tumor, which is always aggressive. Although co-occurrence of these lesions has been reported, this paper describes a homogenous combination of <em>atypical</em> AOT and ameloblastomatous proliferation with some malignant microscopic features. To date, A dozen cases or slightly more of this uncommon composite odontogenic tumor have been, quite correctly, reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The major concern about adenoid ameloblastoma is its biological behaviour. The existing literature says that adenoid ameloblastoma is a locally aggressive odontogenic tumor with a high recurrence rate ranging from 45.5 to 70% [ 8 , 10 , 14 , 15 ]. Loyola et al reported one of his cases showing a maximum of nine recurrences over a period of 19 months.…”
Section: Introductionmentioning
confidence: 99%
“…The major concern about adenoid ameloblastoma is its biological behaviour. The existing literature says that adenoid ameloblastoma is a locally aggressive odontogenic tumor with a high recurrence rate ranging from 45.5 to 70% [ 8 , 10 , 14 , 15 ]. Loyola et al reported one of his cases showing a maximum of nine recurrences over a period of 19 months.…”
Section: Introductionmentioning
confidence: 99%